Mucoadhesive Nanosystems for Nose-to-Brain Drug Delivery in the Treatment of Central Nervous System Diseases - Di Filippo, Leonardo Delello [UNESP] (2022)
The diseases affecting the Central Nervous System (CNS) can have varied etiopathology, but they have in common silent progression, global incidence, and significant impacts on the quality of life of patients and public health systems. With the advance of biomedicine and pharmaceutical technology, new and more modern diagnostic methods and treatments were developed, repurposing the use of drugs currently available for the treatment of CNS diseases. An attractive approach is the use of alternative drug delivery platforms, such as nanocarriers, and less invasive administration routes, such as the noseto-brain, extensively explored for the delivery of drugs into the CNS. Despite many promising results, the nose-to-brain route has some physiological limitations that make it difficult to deliver drugs satisfactorily to exert therapeutic activity in the CNS. To overcome these limitations, nanostructured systems with mucoadhesive properties have stood out over the last few years in pharmaceutical R&D. In this review; we discuss how the noseto-brain route limitations can influence the delivery of drugs to the CNS and highlight the benefits that mucoadhesion can bring to these nanostructured systems. The main findings in the literature are brought together and discussed critically, focusing on how mucoadhesion can improve the biopharmaceutical properties of molecules used in the clinic, as well as their biological performance. Finally, conclusions are drawn about the points of strength of mucoadhesive nanosystems and the points that still need attention to successfully use the nose-to-brain route for the treatment of diseases that affect the CNS.